Electronic Structure for C4’-Substituted Stavudine: ab initio and DFT Investigation - A.S. Alameed, Karrar; Shareef, Falah (Asian Journal of Chemistry, 2013)
In this work, we present the result for electronic structure properties of the stavudine and it’s 4'-substituents molecules that have involved pseudorotation angle parameters for five sugar member ring, frontal orbital, electrostatic potential maps and total energies, as well as, potential energy surfaces of exocylic rotation angles at DFT and ab initio level theories. Comparisons to D4T and 4’substituted ones have the major concern of this report. Five sugar member rings of syn conformers are more planar corresponding to anti ones and the substitution shows a different a trends on the two conformations. The substitution at C4' position not cause a significant changes in gap values, whereas, the substitution lead to decrease dihedral angle (c).